INDEKS PLAK GIGI SEBELUM DAN SESUDAH BERKUMUR SEDUHAN THE HIJAU ANAK UMUR 10 TAHUN DI MIN 1 LAMPUNG BARAT - Lies Elina; Desi Andriyani; Erin Istiandani (Poltekkes Kemenkes Medan, 2024)
Dental plaque is a soft deposit that adheres tightly to the tooth surface. Dental plaque on the tooth surface can trigger dental caries. This requires good efforts to reduce oral diseases caused by dental plaque. Mechanical plaque control methods are regular brushing and the use of dental floss. One way to prevent plaque chemically is to use mouthwash such as green tea brew, because it contains polyphenolic compounds that can reduce the formation of dental plaque. Purpose of the study: to determine the effect of gargling green tea brew in reducing the plaque index. Research. Methods: This type of research is pre-experimental with a One-Group Pretest Posttest design with a sample size of 52 students aged 10 years. Results: Data analysis using the Wilcoxon statistical test. The results of the Wilcoxon statistical test showed a significant difference in plaque index scores between before and after gargling green tea brew with a P value of 0.000 (<0, 05). This means that there is a difference. Conclusion: There is an effect of gargling green tea brew on plaque index in 10-year-old children at MIN 1 West Lampung.